Efficiency of CIDR-Based Protocols Including GnRH Instead of eCG for Estrus Synchronization in Sheep - Paula Martinez-Ros; Antonio Gonzalez-Bulnes (Animals, 2019)
The present study examined, for meat sheep (Segureña breed; 2–5-years old, mean body score of 3.5 ± 0.5), the timings of onset of estrus behavior, preovulatory luteinizing hormone (LH) surge and ovulation, and the ovulation rate and fertility obtained after insertion of controlled internal drug release (CIDR) devices for 5 days plus treatment with equine chorionic gonadotrophin (eCG; single dose at CIDR removal, n = 19 ewes) or gonadotrophin-releasing hormone (GnRH, either in a single dose at 56 h after CIDR removal, group CIDR-GnRH, n = 19 ewes; or in one dose at CIDR insertion and another dose 56 h after CIDR removal, group GnRH-CIDR-GnRH, n = 19 ewes). In all the ewes, the appearance of estrus behavior ranged between 84% and 90% and all females showing estrus signs had subsequent preovulatory LH peaks and ovulations. Onset of these events was earlier in the CIDR-eCG group than in the CIDR-GnRH and GnRH-CIDR-GnRH groups (p < 0.05). These differences were mainly determined by the onset of estrus behavior, since timing and intervals of LH peak and ovulation were similar among treatments. In fact, the range of ovulations was narrower in the GnRH-CIDR-GnRH group, which suggests better synchronization of follicular growth (p < 0.05). In conclusion, protocols with two doses of GnRH offer similar yields to eCG protocols.